Professional Knowledge and Skills: Institutional Aspects and Challenges in the Context of Current and Future Labor Market in Bulgaria - Atanassova, Margarita; Vladimirova, Katia (Research Papers, 2014)
Professional knowledge and skills development as a key component of human capital has traditionally been subject to policies in employment, education and training and social dialogue both the European Union (EU) and in Bulgaria. Theoretical research and practice highlight the construction and improvement of professional knowledge and skills as a complex process which is characterized by an institutional framework including both the legal basis and relevant public bodies and strategic and program documents.General characteristics of the institutional framework are considered in the context of the dynamic socio-economic environment in Bulgaria in recent years. In this paper are presented the main aspects of institutional framework of the professional knowledge and skills improvement process in Bulgaria from the perspective of the state and development of the labor markets and the policies on employment, education and training including to accent the growing role of social partners. Key features of the regulatory framework, institutions and strategic documents in the field of vocational education and training, employment and participation of organizations of employers and workers in the formation and implementation of policies in these areas in Bulgaria are consistently presented. Based on this research number of challenges to the development of vocational education and training, employment and social dialogue in Bulgaria in the context of the dynamics of the labor market were outlined.